The Effect Of Activity, Profitability And Leverage Ratios On The Timeliness Of Financial Reporting - Adelia Alvionita; Adrie Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
The purpose of conducting this research is to analyze the effect of Activity Ratio, Profitability, and Leverage on the Timeliness of Financial Reporting both simultaneously and partially. The dependent variable (Y) that the researcher chose is the Timeliness of Financial Reporting, which is measured through the use of a dummy, with a score of 0 for those who are not on time and 1 for those who are on time. The object applied is the Consumer Goods sub-sector companies listed on the IDX in 2019 – 2022. The sample determined is 35 companies with the research period 2019 – 2022 through the use of Purposive Sampling. The data to be analyzed is the secondary type. Researchers here use the Logistic Regression Analysis method. The results obtained show that simultaneously the Activity Ratio, Profitability and Leverage have a significant effect on the Timeliness of Financial Reporting. Then partially Leverage has a negative effect while Activity and Profitability do not affect the Timeliness of Financial Reporting.